Dimensional Analysis and Optimization of 3-DOF Parallel Bionic Mechanical Leg - Wang Xiaolei; Jin Zhenlin; Li Xiaodan; Liu Xiang (Jixie chuandong)
A new kind of parallel bionic mechanical legs is put forward. The dimension synthesis and optimization about the mechanical leg structure is completed. The position vector model of the mechanical legs is established. The leg position inverse solution and velocity mapping equation are deduced,the velocity Jacobian matrix is obtained. The space evaluation indexes and movement dexterity indexes of the mechanical leg are established. By using space model technology,the influence laws of the structure parameter on the working space evaluation indexes and motion dexterity indexes of the mechanical leg are analyzed. Combining with the technology of processing and assembling,the multiple target probability parameter optimization method based on performance map is applied to select a set of reasonable structural parameters,which lays a solid foundation for statics and dynamics analysis,stiffness analysis,trajectory planning and motion control of the bionic mechanical leg.